A social psychology of protest individuals in action - Stekelenburg, Jacquelien van 1966-; Klandermans, Bert 1944- (Cambridge University Press, 2023)
Protest is typically rare behavior, yet the ﬁrst decade of the twenty-ﬁrst century has been named the era of protest. Successful protests bring masses to the streets, and the emergence of social media has fundamentally changed the process of mobilization. What protests need to be successful is demand (grievances, anger, and indignation), supply (protest organizations), and mobilization (eﬀective communication networks). Motivation to participate can be instrumental, expressive, and identity driven, and politicized collective identity plays an important role in the dynamics of collective action. This volume brings together insights from social psychology, political psychology, sociology, and political science to provide a comprehensive and up-to-date analysis of protest participation, particularly to the question of why some people protest while others do not. It is essential reading for scholars interested in the social and political psychology of individuals in action
Literaturverzeichnis: S. 238-273
Keywords: Protest movements / Psychological aspects; Social psychology